Hyperexcitability of inferior colliculus neurons caused by acute noise exposure. Issue 2 (14th November 2012) - Niu, Yuguang; Kumaraguru, Anand; Wang, Rongguang; Sun, Wei
Abstract Noise exposure is one of the most common causes of hearing loss. Recent studies found that noise exposure‐induced cochlear damage may change the excitability and tonotopic organization of the central auditory system (CAS). This plasticity was suspected to be related to tinnitus and hyperacusis. However, how cochlear damage affects CAS function and causes these neurologic diseases is still not clear. CAS function is activity dependent, so we hypothesize that a restricted cochlear lesion might disrupt the balance of excitation and inhibition in the CAS and thereby affect its neural activity. To test this hypothesis, we studied the effects of narrow‐band noise exposure on the firing properties of neurons in the inferior colliculus (IC), which has complex neural circuits and plays an important role in sound processing. We found that noise exposure (20 kHz, 105 dB SPL, 30 min) caused a dramatic decrease of the characteristic frequency in about two‐thirds of high‐frequency neurons with/without causing a significant threshold shift. The noise exposure also caused an increase in firing rate of the low‐frequency neurons at suprathreshold levels, whereas it dramatically decreased the firing rate of the high‐frequency neurons. Our results suggest that acute high‐frequency noise exposure may increase low‐frequency responsiveness by causing hyperexcitability of low‐frequency neurons. The functional change of the low‐frequency neurons may be related to the disruption of side‐band inhibition at the noise exposure frequencies caused by cochlear damage. © 2012 Wiley Periodicals, Inc.